Effects of dietary monoterpene, myrcene, administration on immune- and health-related genes expression in common carp gill following exposure to copper sulfate - Seyyed Morteza Hoseini (2020)
© 2020 Elsevier Ltd The present study assessed the potential benefits of myrcene administration to suppress negative effects of copper exposure on immune-, antioxidant-, tight junction-, stress- and osmoregulatory-related gene expressions in common carp (Cyprinus carpio) gill. Fish were fed with diets containing 0% (control), 0.5% (M0.5) and 1% (M1) myrcene for 6 weeks, and then, exposed to 0.25 mg/L copper for further two weeks. The fish gill samples were taken for gene expression assays after six and eight weeks. The results showed that there were interaction effects of myrcene levels and copper exposure on superoxide dismutase (sod), catalase (cat), glutathione peroxidase (gpx), glutathione-s-transferase (gst), glutathione reductase (gr), heat shock protein-70 (hsp70), interleukin 1-beta (il1b), interleukin 10 (il10), tumor necrosis factor-alpha (tnfa), occludin (occl), caludin 3 (cld3), caludin 7 (cld7), and Na+-K+-ATPase (nka) genes expressions. Overall, the M0.5 treatment had significantly lower antioxidant genes expression, and higher hsp70, cytokines, tight-junction proteins, and nka genes expression, compared to the control treatment, before copper exposure. Copper exposure significantly down-regulated most of the tested genes (except il10), however, the M0.5 treatment had significantly higher antioxidant (except gpx), hsp70, cld7, and nka gene expression compared to the control treatment. The M1 treatment showed fluctuated antioxidant gene expressions, down-regulated gene expression of the pro-inflammatory cytokines, and occl, and up-regulation of cld3 gene expressions, before copper exposure. After copper exposure, this treatment had significantly higher gr and cat expression compared to the control; moreover, there was a marked up-regulation in il10 gene expression in this treatment, which was the highest value among all treatment combinations. In conclusion, copper exposure significantly down-regulates antioxidant-, inflammatory-, and tight junction-related along with hsp70 and nka genes expression in common carp gills. Pre-treatment with 0.5% myrcene is beneficial to suppress such negative effects, probably due to its antioxidant properties. However, myrcene administration must be done with caution, as higher levels may interfere with antioxidant and immune defenses.